2016
DOI: 10.1007/s00464-016-4754-8
|View full text |Cite
|
Sign up to set email alerts
|

When is mesh fixation in TAPP-repair of primary inguinal hernia repair necessary? The register-based analysis of 11,230 cases

Abstract: Whereas for TEP the guidelines do not recommend mesh fixation on the basis of meta-analyses regardless of the defect size, for TAPP mesh fixation can be omitted only up to a defect size of 3 cm because of the paucity of studies on this topic. Hence, this study now seeks to explore this subject on the basis of prospective data from the Herniamed Hernia Registry. In the period September 01, 2009, to January 31, 2014, 11,228 male patients were operated on with the TAPP technique for a primary unilateral inguinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 21 publications
1
45
0
6
Order By: Relevance
“…These results build on our previously published early experience on this technique . A consistent rate of recurrence in groin hernia repair is difficult to determine in the literature, with a range from 0.88% to 15% being reported . A hernia registry of 11 228 patients revealed a recurrence rate with mesh fixation of 0.88% at 1 year, while no mesh fixation had a recurrence rate of 1.1% without a significant difference in unadjusted analysis .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These results build on our previously published early experience on this technique . A consistent rate of recurrence in groin hernia repair is difficult to determine in the literature, with a range from 0.88% to 15% being reported . A hernia registry of 11 228 patients revealed a recurrence rate with mesh fixation of 0.88% at 1 year, while no mesh fixation had a recurrence rate of 1.1% without a significant difference in unadjusted analysis .…”
Section: Discussionsupporting
confidence: 61%
“…A consistent rate of recurrence in groin hernia repair is difficult to determine in the literature, with a range from 0.88% to 15% being reported . A hernia registry of 11 228 patients revealed a recurrence rate with mesh fixation of 0.88% at 1 year, while no mesh fixation had a recurrence rate of 1.1% without a significant difference in unadjusted analysis . A Cochrane systematic review reported a recurrence risk of 4% in non‐mesh repair and 1–3% in mesh repair …”
Section: Discussionmentioning
confidence: 99%
“…Actualmente las guías publicadas por sociedades vinculadas a la especialidad recomiendan, tanto para la técnica TEP o eTEP como para el abordaje TAPP, considerar la no fijación de la malla en aquellas hernias tipo L I, II, M I y II de la clasificación de la Sociedad Europea de la Hernia (SEH) [5][6][7] .…”
Section: Introductionunclassified
“…4,6 Fixation of prosthetic mesh with titanium tacks in laparoscopic hernioplasty helps to reduce recurrence. 1,7 However it is reported that it may associate with increase in post-operative pain and discomfort. Therefore numerous studies have been focused on the use of alternative approaches for mesh fixation, such as use of suture or fibrin sealant glue fixation.…”
Section: Introductionmentioning
confidence: 99%